1989
DOI: 10.1073/pnas.86.1.177
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin architecture and nuclear RNA.

Abstract: The maintenance of normal chromatin morphology requires ongoing RNA synthesis. We have exmned the role of RNA in chromatin organization, using selective detergent extraction of cells, RNA synthesis inhibitors, and enzymatic digestion of nuclear RNA. Comparison of extracted and unextracted cells showed that the important features of chromatin architecture were largely unchanged by the extraction procedure. Normally, chromatin was distributed in small heterochromatic regions and dispersed euchromatic strands. Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(120 citation statements)
references
References 39 publications
3
117
0
Order By: Relevance
“…We have confirmed this result (Fig. 1G), but unfortunately micrococcal nuclease is known to digest the RNA (21), and this process elicits nuclear rearrangements superficially reminiscent of those occurring in apoptosis (22). Recent reports using a variety of approaches suggest that alterations in chromatin may occur in the absence of internucleosomal cleavage (4,23,24).…”
Section: Resultssupporting
confidence: 73%
“…We have confirmed this result (Fig. 1G), but unfortunately micrococcal nuclease is known to digest the RNA (21), and this process elicits nuclear rearrangements superficially reminiscent of those occurring in apoptosis (22). Recent reports using a variety of approaches suggest that alterations in chromatin may occur in the absence of internucleosomal cleavage (4,23,24).…”
Section: Resultssupporting
confidence: 73%
“…Most dramatically, global inhibition of transcription induces a general compaction of interphase chromatin (Nickerson et al, 1989). In agreement with this, transcription at engineered gene arrays leads to chromatin decompaction (Tsukamoto et al, 2000;Müller et al, 2001).…”
Section: Introductionmentioning
confidence: 50%
“…Early experiments revealed that RNA is localized to regions of intermediate and low DNA concentration (Monneron and Bernhard, 1969;Fakan and Bernhard, 1971). A causal link between RNA and chromatin organization was first shown by global RNA digestion, which induced nucleuswide chromatin compaction (Nickerson et al, 1989). Specific RNAs have also been implicated in chromatin organization.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our data reinforce the emerging picture that a substantial subset of long ncRNAs, including Evx1as and Hoxb5/6as, has a chromatin-related function. In fact, eukaryotic chromatin is comprised of a large mass of associated RNAs that is essential for its general structural organization (Nickerson et al 1989;Rodriguez-Campos and Azorin 2007) and likely mediates a number of chromatin-regulation processes.…”
Section: Discussionmentioning
confidence: 99%